Informal Care and the Importance of Institutional Support in Alzheimer’s Disease: Caregivers’ Experience with Mavi Ev - Nilüfer Korkmaz Yaylagül; Aslı Gözde Akış; Hande Barlın (İstanbul Üniversitesi Sosyoloji Dergisi)
Caring for patients with Alzheimer’s disease is a challenging process. Caring for Alzheimer’s patients results in physical, psychological, and economic burdens for caregivers. This has the potential to affect patients’ and care recipients’ quality of life. While many caregivers have difficulty accessing adequate information and support, they also remain reluctant to benefit from institutional support. Nonetheless, institutional support has become increasingly important for caregivers in terms of the sustainability of care, as the care process is long and exhausting. This study focuses on the experiences of caregivers receiving services from an adult daycare center that institutionally supports Alzheimer’s patients and their caregivers. The study aims to understand the effect of institutional support on the care process based on Andersen’s behavioral model of healthcare utilization. Embodying a qualitative method, the study benefits from thematically analyzing the data collected through faceto-face interviews made with 30 caregivers. The results from the study show caregivers to be satisfied with the institutional support and this support to contribute to meeting the respite they need most in care. Daycares are a new service in Turkey and are an alternative service model able to positively contribute to the informal care process.